2017
DOI: 10.1186/s41239-017-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate students’ conceptual interpretation and perceptions of haptic-enabled learning experiences

Abstract: Although visualization remains a primary mode of interaction in simulations, touch is the most common way people use to interact with the physical objects. A greater sense of immersion in a learning environment can be reached when the user is able to feel and manipulate objects as compared to only seeing or listening. Despite the affordances of haptic technologies, which could serve as scaffolds for deep conceptual learning, their true potential in education has not been fully harnessed and little research has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Moreover, there is a leap in the number of CC between the pre‐ and posttests for scenarios 3 and 4 while the number of CN remained the same. These results show similarity with Han and Black , Shaikh et al , and Magana et al, studies reported that embodied haptic experiences may facilitate learning physics concepts via building a solid cognitive foundation.…”
Section: Discussion and Implications For Teaching And Learningmentioning
confidence: 99%
“…Moreover, there is a leap in the number of CC between the pre‐ and posttests for scenarios 3 and 4 while the number of CN remained the same. These results show similarity with Han and Black , Shaikh et al , and Magana et al, studies reported that embodied haptic experiences may facilitate learning physics concepts via building a solid cognitive foundation.…”
Section: Discussion and Implications For Teaching And Learningmentioning
confidence: 99%
“…Science education is not the exception. Researchers who have investigated the educational potential of haptic technologies argued that the sense of touch can enhance conceptual understanding by making more accessible difficult concepts in science and engineering by visualizing them and enhancing their exploration (Jones & Magana, ; Shaikh, Magana, Neri, Escobar‐Castillejos, Noguez & Benes, ). Embodied Cognition is the underlying theory that supports this notion.…”
Section: Embodied Cognition and Implications For Learning With Hapticmentioning
confidence: 99%
“…IT-aided learning tools have been found very effective in improving the learning outcomes of students for various subjects such as statistics (Peterson, 2016), mathematics (Spradlin & Ackerman, 2010), science (Shaikh et al, 2017;Zhu, Valcke, & Schellens, 2009), technology (Lee, Barker, & Kumar, 2016), education (Choi & Yang, 2011), medicine (Patterson, Kilpatrick, & Woebkenberg, 2010), nursing (Öztürk & Dinç, 2014), and language (Rahimi & Miri, 2014). Several studies have demonstrated that ITmediated teaching options like flipped classrooms help students outperform their traditional counterparts in biology (Marcey & Brint, 2013), physiology (Tune et al, 2013), and human-computer interaction courses (Day & Foley, 2006).…”
Section: Subject Typementioning
confidence: 99%